Exploring the great outdoors - Mayer, Mercer, 1943- (Mayer, Mercer, 1943- Little Critter book., 2019)
Little Critter and his classmates take a field trip into the woods to study their natural surroundings. They see little bugs, big trees, and lots of animal tracks. There's so much to see and do and explore! Little Critter discovers that there are plenty of surprises in store when it comes to the great outdoors.